2008
DOI: 10.1002/bies.20775
|View full text |Cite
|
Sign up to set email alerts
|

Do vertebrate neural crest and cranial placodes have a common evolutionary origin?

Abstract: Two embryonic tissues-the neural crest and the cranial placodes-give rise to most evolutionary novelties of the vertebrate head. These two tissues develop similarly in several respects: they originate from ectoderm at the neural plate border, give rise to migratory cells and develop into multiple cell fates including sensory neurons. These similarities, and the joint appearance of both tissues in the vertebrate lineage, may point to a common evolutionary origin of neural crest and placodes from a specialized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 112 publications
0
79
1
Order By: Relevance
“…The 'binary competence' model of neural crest/cranial placode induction proposed a segregation of NC and cranial placode competence at the neural plate border stage (Schlosser, 2008). Contrary to this model, we found that WNT directs a segregation of early NC and cranial placode cell fates prior to the induction of the neural plate border markers; pB genes such as GBX2, ZEB2, SP5 and ZIC3 are induced by WNT/CTNNB1 signaling 1 or 2 days prior to induction of the NB genes PAX3, PAX7 and MSX1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 'binary competence' model of neural crest/cranial placode induction proposed a segregation of NC and cranial placode competence at the neural plate border stage (Schlosser, 2008). Contrary to this model, we found that WNT directs a segregation of early NC and cranial placode cell fates prior to the induction of the neural plate border markers; pB genes such as GBX2, ZEB2, SP5 and ZIC3 are induced by WNT/CTNNB1 signaling 1 or 2 days prior to induction of the NB genes PAX3, PAX7 and MSX1.…”
Section: Discussionmentioning
confidence: 99%
“…3D,E; Leung et al, 2013) further supporting the idea that segregation of NC and cranial placode fates occurs very early in our cultures. It has been suggested that NC competence segregates with the neuralized domain of the ectoderm (Pieper et al, 2012;Schlosser, 2008). We have examined the expression dynamics of a number of neural-related transcripts, including LHX2, PAX6, SOX1, SOX2, OTX2 and HES5 (Greber et al, 2011;Hou et al, 2013;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7A-C, E,M). Since placodal and neural crest cells both originate from the ectoderm at the neural plate border and give rise to migratory cells developing into multiple cell fates (Schlosser, 2008), they may also share their response to semaphorin signals.…”
Section: Semaphorins Are Expressed In the Cranial Neural Crest Area Amentioning
confidence: 99%
“…The NPB and PPE give rise to the neural crest and placode, respectively, both of which undergo epithelial-to-mesenchymal transition/delamination, migrate in prototypical paths, and give rise to the peripheral nervous system (PNS) and many other cell types (3,4). However, the NPB and PPE also have many different features (5). For example, the PPE is confined to the anterior half of embryos and does not contribute to the central nervous system (CNS), whereas the NPB is the lateral border of the whole neural plate and consists not only of progenitors for the PNS but also those for the CNS in the dorsal neural tube.…”
mentioning
confidence: 99%